2016
DOI: 10.5539/ass.v12n9p149
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Maintenance of a Nature Conservation Area: A Case of Mount Wilhelm, Papua New Guinea

Abstract: Ecosystem services that are not traded on markets contribute to human wellbeing however their economic value is not well known and research is required to reveal it. This paper reports on a study of willingness to pay (WTP) for the maintenance of Mount Wilhelm by urban residents and socio-economic factors influencing it. The possibility of developing an ecotourism strategy that could generate benefits for local are discussed. The data were obtained from questionnaire and personal interviews of residents of Kun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…According to the policy analysis, it was found that there are many specific issues in the scenic and historic areas that need attention. Firstly, good operation and maintenance management models are very important to promote public willingness to protect scenic resources [118] and many countries have paid high attention to them [119][120][121]. Scenic and historic areas also need to pay more attention to maintenance management.…”
Section: Discussionmentioning
confidence: 99%
“…According to the policy analysis, it was found that there are many specific issues in the scenic and historic areas that need attention. Firstly, good operation and maintenance management models are very important to promote public willingness to protect scenic resources [118] and many countries have paid high attention to them [119][120][121]. Scenic and historic areas also need to pay more attention to maintenance management.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial and necessary to investigate the visitor-related factors underlying this monetary valuation of natural resource protection [34], which improves WTP estimation efficiency and achieves geopark management and conservation. First, previous studies examined the influences of demographic variables (i.e., age, income) on WTP in the context of resource conservation in ecotourism and geotourism [12,25,26]. However, existing surveys exhibit contradictory results in terms of explaining those relationships.…”
Section: Determinants Of Willingness To Paymentioning
confidence: 99%
“…For instance. Ezebilo [12] indicated no significant relationships between age and WTP for ecotourism resource conservation, whilst a statistical coefficient of age was found to have positive effects on WTP in terms of protecting natural resources [5]. Income level was one of the most widely recognized predictors of WTP for nature conservation [17,35]; nonetheless, Patti [31] reported that income was irrelevant to WTP for environment protection in ecotourism.…”
Section: Determinants Of Willingness To Paymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that sociodemographic variables (Kosz, 1996, Lindsey and Holmes, 2002, Bal and Mohanty, 2014, Ezebilo, 2016, and tourist behaviour (Kamri et al, 2017, Adamu et al, 2015 influenced WTP. Differences in people's WTP may be influenced by certain demographic and psychographic factors.…”
Section: Introductionmentioning
confidence: 98%